Nanosecond Laser‐Assisted Nitrogen Doping of Graphene Oxide Dispersions. Issue 8 (27th February 2017) - Kepić, Dejan; Sandoval, Stefania; Pino, Ángel Pérez del; György, Enikö; Cabana, Laura; Ballesteros, Belén; Tobias, Gerard
Abstract: N‐doped reduced graphene oxide (RGO) has been prepared in bulk form by laser irradiation of graphene oxide (GO) dispersed in an aqueous solution of ammonia. A pulsed Nd:YAG laser with emission wavelengths in the infrared (IR) 1064 nm, visible (Vis) 532 nm, and ultraviolet (UV) 266 nm spectral regions was employed for the preparation of the N‐doped RGO samples. Regardless of the laser energy employed, the resulting material presents a higher fraction of pyrrolic nitrogen compared to nitrogen atoms in pyridinic and graphitic coordination. Noticeably, whereas increasing the laser fluence of UV and Vis wavelengths results in an increase in the total amount of nitrogen, up to 4.9 at. % (UV wavelength at 60 mJ cm −2 fluence), the opposite trend is observed when the GO is irradiated in ammonia solution through IR processing. The proposed laser‐based methodology allows the bulk synthesis of N‐doped reduced graphene oxide in a simple, fast, and cost efficient manner. Abstract : N‐doped reduced graphene oxide samples can be prepared in a simple, fast and energy‐efficient manner by laser‐assisted synthesis.